Development of Art Learning Supplement Books for Middle School Students - Purwaningsih, Endah; Fatirul, Ach. Noor; Hartono, Hartono (International Journal for Educational and Vocational Studies, 2020)
Fine art, creative, and innovative are the components are interlinked and inseparable on the one hand, the students are also required to love and raise the value of art subjects. In line with this, the peseta students must also have skills that are competent for the results of his art deserves to be appreciated, economic value, and has a high resale value in the community around.That it is necessary to supplement the Book Development has the feasibility to use on learning in junior high art is Development Education Supplement Book Arts For junior high school students. The book is said to be feasible on the basis of the results of validation of educational materials experts art creative and innovative. The results of the feasibility design validation scored 90.9% and validation of the feasibility of fine art materials gained 72.6% value. The results of the validation predicate good for fine arts material, it is reflected in the percentage achieved value included in the interval 52% -75%. Books Arts Education Supplement For Junior High School Students. a supplement book learning that can be accepted by the students, the acceptance rate includes aspects of display with a value of 88% and 85% eligibility rate presentation. Small-scale test results entered in the range of 76% -100% value and the whole predicate is very good.